Mortality and cancer incidence among Swedish dock workers--a retrospective cohort study. - Gustafsson, Lars; Wall, Stig; Larsson, L. G.; Skog, B. (Scandinavian Journal of Work, Environment & Health, 1986)
The study originates from the arousal of suspicions that, in connection with loading and unloading work involving the use of trucks, exposure to diesel exhaust fumes may be carcinogenic. This report describes a register study in which a broad mapping of the cause-of-death pattern and cancer morbidity has been carried out through the matching of locally compiled personal data with those from a central register, the Cause-of-Death Register, and the Cancer Register. The results obtained thus far show a low total mortality--irrespective of cause of death--but a tendency towards an excess risk for cancer morbidity, mainly due to lung cancer.